Ellipsometric study of ion implanted copper surface and its room temperature oxidation - Poperenko, L.V.; Lohner, T.; Stashchuk, V.S.; Khanh, N.Q.; Vinnichenko, M.V.; Yurgelevych, I.V.; Essam Ramadan Shaaban; Nosach, D.V. (Functional Materials, 2005)
The room temperature oxidation of ion-implanted copper surface has been studied ex situ and in situ using ellipsometry. The ellipsometric parameters T and Д were measured at light incidence angle 75° for different wavelength values in the range of 280 to 760 nm using averaging both over two azimuthal zones and single one. The oxide layer was removed from the copper surface during the aluminum ion implantation an then the growth of the newly formed oxide film on the ion implanted surface was studied by ellipsometry. Basing on the spectroellipsometric data, the oxide film thickness has been calculated for two types of copper oxides. Проведены эллипсометрические исследования окисления при комнатной температуре ионно-имплантированных поверхностей меди. Эллипсометрические параметры T и Д измерены при угле падения света 75° для различных величин длины волны света в области 280—760 нм с усреднением как по двум, так и по одной азимутальным зонам. Оксидная пленка с поверхности меди удалялась в процессе ее имплантации ионами алюминия, а затем рост вновь формируемой пленки оксида меди на имплантированной поверхности исследован эллипсометрическим методом. Проведены на основе спектроэллипсометрических данных расчеты толщин пленок для двух типов оксидов меди. Проведено еліпсометричні дослідження окиснення при кімнатній температурі іонно-імплантованих поверхонь міді. Еліпсометричні параметри Т і Д виміряно при куті падіння світла 75° для різних величин довжини хвилі світла в області 280-760 нм з усередненням як за двома, так і за однією азимутальними зонами. Оксидна плівка з поверхні міді розпилювалась у процесі її імплантації іонами алюмінію, і наступний ріст нової плівки оксиду міді на імплантованій поверхні досліджено еліпсометричним методом. На основі спектроеліпсометричних даних розраховано товщину плівок для двох типів оксидів міді.